Karakterisasi Pengecoran Paduan Al-Si-TiB dengan Variabel Suhu Die Casting - Abdus Shomad, Muhammad; Wisnujati, Andika; Mudjijana, Mudjijana (Rekayasa, 2022)
This study describes the microstructure phase and the hardness value produced in metal casting with variations in metal mold temperature with the addition of Ti-B elements. gravity casting, a technique that relies solely on gravity, is used for casting metals. This objective of this study to determine the mechanical properties characterization of specimens using die casting molds by varying the mold temperature between 250°C, 350°C, 450°C and the addition of 0.05% Ti-B alloying elements. In addition, this research can determine the right temperature for metal casting by gravity casting method. The material used in this research is recycle piston Al-Si (series 4xxx). The results of hardness testing at a temperature of 250°C have produced 123.9 HVN. The microstructure of the Al-Si-TiB alloy material has dense grain boundaries. This is because the casting with the addition of the TiB element functions as a grain refiner and reduces porosity in the microstructure. So, the smaller the porosity, the stronger the hardness of the specimen or material. This is because at low mold temperatures, the metal casting process will freeze faster, resulting in higher hardness. In addition, the increasing temperature of the die casting mold has a tendency to change the eutectic structure of silicon to primary silicon.